2020
DOI: 10.1038/s41598-020-77209-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vitamin D status in Kenyan calves

Abstract: Vitamin D plays a critical role in calcium homeostasis and in the maintenance and development of skeletal health. Vitamin D status has increasingly been linked to non-skeletal health outcomes such as all-cause mortality, infectious diseases and reproductive outcomes in both humans and veterinary species. We have previously demonstrated a relationship between vitamin D status, assessed by the measurement of serum concentrations of the major vitamin D metabolite 25 hydroxyvitamin D (25(OH)D), and a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…Therefore, our results suggest that although IL-8 genotype shapes Vit D responses, other molecular factors are associated with the Vit D status in cattle. In fact, a recent genome-wide association study in African calves had found serum 25OHD concentration to be under polygenic control 33 . Therefore, environmental and host factors can contribute to changes in the Vit D status of cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that although IL-8 genotype shapes Vit D responses, other molecular factors are associated with the Vit D status in cattle. In fact, a recent genome-wide association study in African calves had found serum 25OHD concentration to be under polygenic control 33 . Therefore, environmental and host factors can contribute to changes in the Vit D status of cattle.…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted heavier sheep would have higher vD 2 concentrations, since this suggests these sheep are better foragers. Further, associations with total vD and vD 3 concentrations and coat colour have previously been documented in other ruminants (Callaby et al, 2020;Zhou et al, 2019) and so we expected sheep with dark coats to have lower concentrations of these vitamin D metabolites. Although solar radiation is a considerable driver of vitamin D status in human populations (Holick, 2007), we only had data for 6 years in this population; individual exposure levels were highly similar between all sheep measured within a given year due to the small range of sampling dates in August.…”
Section: Phenotypic Associations With Vitamin D Concentrationsmentioning
confidence: 83%
“…We found that Soay sheep females had higher vitamin D concentrations, but only after accounting for weight. A study in cattle found no association between sex and total vD concentrations (Callaby et al, 2020), suggesting that the sex differences in humans may be due to differences in behaviour and diet which do not occur in domestic ruminants. Third, we found that dark coated sheep had considerably lower total vD and vD 3 , which is consistent with studies in other sheep breeds (Zhou et al, 2019) and cattle (Callaby et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En contraste, Hymøller y Jensen (2010) postulan que la piel es la fuente principal de esta vitamina en el ganado en pastoreo. En relación a la síntesis cutánea, se ha reportado que los terneros con pelaje de colores más oscuros presentan concentraciones séricas de 25(OH)D total y 25(OH)D 3 más bajas que los terneros con pelaje mixtos (Callaby et al, 2020).…”
Section: Niveles De Vitamina Dunclassified